Economic liberalization and globalization vs. India's poor - Matthias Oschinski (Transformation, Integration and Globalization Economic Research (TIGER), 2003)
Today, many in the national and international NGO community perceive globalization and economic liberalization as a threat claiming that it widens inequalities and increases overall poverty. While it is true that inequality is on the rise in a rapidly globalizing world the real culprit is not globalization itself but rather a lack of economic reforms and economic liberalization. This paper aims to show that many in the international NGO community confuse cause and effect. The root cause of poverty is not economic liberalization - it is the exclusion of the poor from the market economy. Hence, in order to fight poverty, NGO's should not oppose globalization and economic liberalization but rather instrumentalize them in favor of the poor.
Keywords: 330; Globalisierung; Handelsliberalisierung; Armut; Nichtregierungsorganisation; Indien